2022
DOI: 10.1002/ajim.23416
|View full text |Cite
|
Sign up to set email alerts
|

Elevated exposures to respirable crystalline silica among engineered stone fabrication workers in California, January 2019–February 2020

Abstract: Background Workers fabricating engineered stone face high risk for exposure to respirable crystalline silica (RCS) and subsequent development of silicosis. In response, the California Division of Occupational Safety and Health (Cal/OSHA) performed targeted enforcement inspections at engineered stone fabrication worksites. We investigated RCS exposures and employer adherence to Cal/OSHA's RCS and respiratory protection standards from these inspections to assess ongoing risk to stone fabrication workers. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The mainstay of managing patients with silicosis is minimizing further exposure. This can be challenging, as inadequate dust suppression and poor compliance with respiratory protection regulations are common in this industry . The NIOSH hierarchy of controls for worker safety prioritizes the elimination of hazardous exposure, followed by use of engineering controls; personal protective equipment is least effective .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mainstay of managing patients with silicosis is minimizing further exposure. This can be challenging, as inadequate dust suppression and poor compliance with respiratory protection regulations are common in this industry . The NIOSH hierarchy of controls for worker safety prioritizes the elimination of hazardous exposure, followed by use of engineering controls; personal protective equipment is least effective .…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturers deliver slabs to shops where fabricators cut, sand, and polish the material and generate levels of crystalline silica dust that may be hazardous. Fabrication is frequently performed in shops where ventilation, dust control methods, and personal protective equipment are inadequate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these findings are based on worker report, they are consistent with our prior review of Cal/OSHA citations issued as a result of this SEP, which found that 72% of employers were cited for violations of the silica standard. 4 Our study had several limitations. Findings were based on worker self-report; workers may have limited recall of past work practices and may also have been hesitant to report perceived workplace safety issues to Cal/OSHA inspectors.…”
mentioning
confidence: 91%
“…We have previously reported high prevalence of silicosis among workers in this industry, and our prior analysis of inspection data from a California Division of Occupational Safety and Health (Cal/OSHA) silica Special Emphasis Program (SEP) found widespread silica overexposure and Cal/OSHA regulation violations at California stone fabrication workplaces. [2][3][4] As part of the SEP, Cal/OSHA also conducted worker interviews, the results of which have not previously been reported. Prompted by Tustin et al's findings and our prior work, we analyzed data from these interviews to evaluate worker-reported silica exposures and workplace protections, including utilization of medical surveillance, in engineered stone fabrication workplaces in California.…”
mentioning
confidence: 99%